Molecular dynamics study of water-HBN nanofluid - Akıner, Tolga. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
This study considers the molecular simulations of nanoﬂuids and the goal is to investigate the thermomechanical mechanisms in nanoscale thermal transport. The enhanced thermal conductivity and limited shear viscosity increase is the fundamental phenomena that makes nanoﬂuids as a hot research topic of the recent thermal-ﬂuid and nanoscience literature, and a potential novel complex liquids for variety of appli cations. The nanoﬂuid problem has been studied from the nanomechanical point of view and molecular dynamics simulations are used to investigate the physical aspects. A water-copper system has been modelled as a benchmark study to understand the nanocolloid concept and the capacity of existing methodologies. Green-Kubo formal ism, pure water system, thermal enhancement and viscosity increase of water-copper nanoﬂuids and Brownian motion eﬀect has been studied and compared with the exper imental results. Potential function improvement has been aimed for a water-hexagonal boron nitride system to obtain a robust mathematical foundation for the molecular dynamics simulations. Therefore, interlayer interactions of hexagonal boron nitride and interface interactions at the water-hexagonal boron nitride interface have been formulated using recent quantum simulation results and experimental data. Thermo mechanical properties of hexagonal boron nitride have been accurately estimated using simulations with derived potentials, and water-hexagonal boron nitride interfacial dy namics have been discussed for the interfacial thermal transport. A new temperature calculation algorithm for non-equilibrium simulations has been introduced and tested for rigid and ﬂexible water model. A new approach has been preliminarily developed to study the agglomeration in nanoﬂuids with orthotropic nanoparticles using simulations and experimental images.
Keywords: Nanofluids -- Simulation methods.